2003
DOI: 10.1097/00002820-200302000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Turning Toward the Psychosocial Domain of Oncology Nursing

Abstract: The purpose of this descriptive exploratory study by the Dutch Oncology Nursing Society was to describe the problem areas in the care of patients who are receiving chemotherapy as perceived by patients and professional caregivers as well as to explore differences between the perceptions of patients and professional caregivers. Three independent samples of 120 patients who are being treated with chemotherapy, 42 chemotherapy prescribing medical specialists, and 68 oncology nurses who are involved in the daily b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
1
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 27 publications
1
12
1
2
Order By: Relevance
“…This differs from Uitterhoeve et al [25] who found that both patients and health professionals were of the belief that less attention was given to patients' relatives. The finding of the present study differs in that patient and family needs are given equal consideration and that family needs are not necessarily being overlooked.…”
Section: Discussioncontrasting
confidence: 67%
See 2 more Smart Citations
“…This differs from Uitterhoeve et al [25] who found that both patients and health professionals were of the belief that less attention was given to patients' relatives. The finding of the present study differs in that patient and family needs are given equal consideration and that family needs are not necessarily being overlooked.…”
Section: Discussioncontrasting
confidence: 67%
“…The recent trend towards out-patient care has resulted in increasing responsibility for families, and exacerbation of their emotional load [24,25]. However, both patients and HPs consider that less attention is generally given to relatives [25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings from a recent descriptive study showed that patients are dissatisfied with the tendency of oncologists and oncology nurses not to pay attention to the emotional consequences of cancer diagnosis and treatment [10]. These findings concur with studies [11][12][13][14][15][16] reporting that the emotional dimension of provider communication is an important factor in determining patient satisfaction.…”
Section: Introductionsupporting
confidence: 61%
“…Professional caregivers appear to be selective in their receptiveness of patients' needs, focus on physical problems and to a much lesser extent on emotional problems and psychosocial needs. This implies that psychological problems and emotional needs are not adequately assessed (Heaven and Maguire, 1997;Sanson-Fisher et al, 2000;Fallowfield et al, 2001) and consequently addressed (Wilkinson, 1991;Dennison, 1995;Ford et al, 1996;Maguire et al, 1996;Heaven and Maguire, 1997;Suchman et al, 1997;Maguire, 1999;Osse et al, 2000;Andersen and Adamsen, 2001;Uitterhoeve et al, 2003).…”
mentioning
confidence: 99%